Case report: Case report and literature review: Treatment of sweat gland carcinoma - Dai, Yuhong; Feng, Jin; Zhou, Xiao (Frontiers in Oncology, 2023)
Background Sweat gland carcinoma (SGC) is a rare neoplasm originating from sweat glands. Surgical resection is the first choice for SGC treatment, and there is no consensus on other treatments for advanced SGC. Methods and result In this case report, we present a case of a female patient with advanced SGC who received surgery; radiotherapy; multiple lines of chemotherapy, which include docetaxel, nedaplatin, albumin-bound paclitaxel, and pemetrexed; and immunotherapy (camrelizumab). The survival time of this patient is 35 months. MRI tumor monitoring indicated that these treatments slowed the progression of the disease. The effectiveness of chemotherapy, radiotherapy, and immunotherapy should be tested for more patients with SGC in the future. Conclusion Although the patient’s tumor was uncontrolled eventually, multiple treatments delayed tumor growth over a period of time, providing ideas for others when choosing regimens.